Ultraviolet Fluorescence Photography—Choosing the Correct Filters for Imaging - Jonathan Crowther (Journal of Imaging, 2022)
Ultraviolet (UV) fluorescence is a valuable tool for the imaging of a wide range of subjects. Like all imaging techniques, the key to success depends on the correct choice of equipment and approach used. In fluorescence photography, a filter is placed in front of the camera lens to block unwanted short-wavelength light from entering the camera, which would compromise the image. However, some filters exhibit fluorescence under UV light and can therefore have the potential to produce a color cast on the image. Filters also vary in how well they block unwanted light. A range of commonly used optical filters was assessed for fluorescence under UV light, and their optical transmission between 250 nm and 800 nm was measured. Finally, a simple method to enable the researcher to determine the fluorescence of the filters that they are using or wish to use for their work is described. The results indicate that the filters tested demonstrated a wide range of fluorescence under UV light and varying degrees of UV blocking. Some filters tested had equivalent or reduced fluorescence compared to Schott KV-418, which is a widely used, but, unfortunately, no longer manufactured UV blocking filter commonly used for fluorescence photography.